2013
DOI: 10.1096/fj.13-242123
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory circuitry of TWEAK‐Fn14 system and PGC‐1α in skeletal muscle atrophy program

Abstract: Skeletal muscle wasting attributed to inactivity has significant adverse functional consequences. Accumulating evidence suggests that peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) and TNF-like weak inducer of apoptosis (TWEAK)-Fn14 system are key regulators of skeletal muscle mass in various catabolic states. While the activation of TWEAK-Fn14 signaling causes muscle wasting, PGC-1α preserves muscle mass in several conditions, including functional denervation and aging. However, it remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 57 publications
3
74
2
Order By: Relevance
“…In this study, we have investigated whether TWEAK-Fn14 axis has a role in regulation of skeletal muscle mass during aging. Consistent with publised reports that skeletal muscle of adult mice express minimial to undetactable levels of Fn14 [16,27], we did not find any histological or biochemical differences in skeletal muscle of 3-month old WT and Fn14-KO mice. However, the expression of Fn14 is signficantly increased in skeletal muscle with advancing age and the differences in fiber size and biochemical changes became evident in skeletal muscle of WT and Fn14-KO mice at the age of 18 months.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we have investigated whether TWEAK-Fn14 axis has a role in regulation of skeletal muscle mass during aging. Consistent with publised reports that skeletal muscle of adult mice express minimial to undetactable levels of Fn14 [16,27], we did not find any histological or biochemical differences in skeletal muscle of 3-month old WT and Fn14-KO mice. However, the expression of Fn14 is signficantly increased in skeletal muscle with advancing age and the differences in fiber size and biochemical changes became evident in skeletal muscle of WT and Fn14-KO mice at the age of 18 months.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, TWEAK has been identified as a key mediator of wasting in denervation [18] and cancer [19]. TWEAK induces muscle RING-finger protein 1 (MuRF1) expression via NF-kB activation [10] (Box 2).…”
Section: Tweakmentioning
confidence: 99%
“…Therefore, our studies are underway to determine the potential role of heightened muscle inflammation in metabolic disturbances among individuals with SCI. Higher TWEAK R in SCI muscle may also cause impaired oxidative metabolism, as recent animal studies (18,36) have demonstrated that TWEAK inhibits skeletal muscle oxidative metabolism via activating the NF-B signaling pathway, which represses PGC-1␣ levels in skeletal muscle. For example, TWEAK KO mice present with higher skeletal muscle mitochondrial content and oxidative phosphorylation capacity via increasing PGC-1␣ levels compared with wild-type mice.…”
Section: E758 Heightened Tweak-tweak R-nf-b Signaling In Sci Musclementioning
confidence: 99%